IMPROVING THE STUDENTS’ LISTENING COMPREHENSION THROUGH ENGLISH SONG OF THE SEVENTH GRADE OF SMP KRISTEN KEFAMENANU - Siahaan, Desta Gloria; Mnaka, Fridensia Nurini; Sahan, Anselmus; Tarigan, Surya Setiadi (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2023)
The purpose of this study was to determine the improvement in listening comprehension of students by using English Songs in class VII students at SMP Kristen Kefamenanu. This research used the quantitative research to find the data and results of test. The subject of this study were 45 students consisting of 25 students and 20 students and the data were collected by using tetst and observation. The data obtained in the first cycle indicated an average score 5.8 with the percentage of students who passed the test was 8.28% while in the second cycle, the average score was 5.58, with the percentage of students who passed the test was 8.5%. Meanwhile, based on the observasion in the first cycle, the students listening comprehension were considered as deficient, and some students could not listen properly to the songs that were played to them. On the other hand, in the second cycle, students showed that they had been able to improve their listening comprehension through the use of English Songs. The results showed that there was an Improving The Students’ Listening Comprehension Of The Seventh Grade Of Smp Kristen Kefamenanu Through Songs.